Fatigue reliability and post-fracture residual capacity of a two-girder steel bridge - Hartung, Lena F., author; Mahmoud, Hussam, advisor; Atadero, Rebecca, committee member; Strong, Kelly, committee member (Colorado State University. Libraries, 2016)
Due to the immense and always increasing traffic volume, bridges are permanently subjected to repetitive loadings. These high numbers of cyclic loads can cause the initiation of fatigue cracks. If these flaws remain undetected they may become through-thickness cracks and further propagate, if left unrepaired, until they eventually lead to fracture of the entire member. The criticality of a full member fracture is not well defined nor agreed upon. Previous failure cases have demonstrated the ability of two-girder steel bridges to withstand full girder fracture of one of the two girders without structural collapse. Other cases, however, have shown the criticality of a complete girder failure on complete system collapse. Due to uncertainties in bridge redundancy and the ability to develop alternative load path, the American Association of State Highway and Transportation Officials (AASHTO) attempts to prevent fracture or collapse by classifying bridges with respect to their redundancy into fracture critical bridges (FCB) and decreasing their inspection periods. However, this leads to higher construction and maintenance costs for the owners of FCBs. Clearly, the level of uncertainty in bridge performance when one of its two girders suffer complete fracture should be represented in a probabilistic manner to evaluate the probability of fatigue crack growth and system collapse. To that end, thesis uses probabilistic analysis to assess the crack propagation behavior in a girder of a two-girder steel bridge by conducting finite element Monte Carlo simulations. The simulations account for the scatter in the load and the resistance by treating those uncertainties as random variables with predefined statistical distributions. Additionally, the post fracture redundancy is evaluated by comparing the resulting equivalent plastic strain to the failure strain of steel. The results show that the bridge provides sufficient redundancy to redistribute the load after full depth fracture a FC member. Furthermore, the results of the probabilistic analyses provide a basis for choosing the inspection intervals for FCBs.
Keywords: finite element analysis; post-fracture redundancy; fatigue reliability; probabilistic analysis; Monte Carlo simulation